Sometimes It Works! The Effect of a Reform of the Short Vocational Track on School-to-Work Transition - Simona Lorena Comi; Mara Grasseni; Federica Origo (Institute of Labor Economics (IZA), 2022)
This paper studies the impact on the length of school-to-work transition of a reform that extended from two to three years the short vocational track in Italy in the early 2000s. In the empirical analysis we use the Two Way Fixed Effect methodology to estimate the impact of the reform, exploiting its staggered implementation across regions. The analysis is restricted to graduates from the short vocational track before and after the reform. The results show that the reform had a positive impact and reduced school-to-work transition by around 5 months (a 24% reduction). Moreover, the new short vocational track proved to be extremely effective for migrants and females, whose school-to-work transition was reduced by 1.4 years and 0.9 years, respectively. In implementing the new short vocational track, some regions adopted a quasi-market organization in which private training institutions competed with public schools. This model proved to be more effective in shortening school-to-work transitions, in particular for migrants. This study makes an important contribution to the literature on the labor-market effect of vocational education by showing that lengthening the short vocational track, and changing the overall content of curricula, can speed up school-to-work transition.
Keywords: I26; I28; J24; 330; school-to-work transition; vocational education; policy evaluation